Sequencing of VDJ genes in Lepus americanus confirms a correlation between VHn expression and the leporid species continent of origin. (August 2019) - Pinheiro, Ana; de Sousa-Pereira, Patricia; Almeida, Tereza; Ferreira, Catarina C.; Otis, Josée-Anne; Boudreau, Melanie R.; Seguin, Jacob L.; Lanning, Dennis K.; Esteves, Pedro J.
Highlights: Leporid antibodies VH genes exhibit highly divergent lineages. These VH lineages, VH a, VH n, sL and sS, are differently used by leporid species. The VH n genes are a conserved ancestral polymorphism. The VH n are used differentially by European leporids and American leporids. The differential usage of VH n may be related with adaptation to different pathogens. Abstract: Leporid VH genes used in the generation of their primary antibody repertoire exhibit highly divergent lineages. For the European rabbit ( Oryctolagus cuniculus ) four VH a lineages have been described, the a1, a2, a3 and a4. Hares ( Lepus spp.) and cottontail ( Sylvilagus floridanus ) express one VH a lineage each, the a2L and the a5, respectively, along with a more ancient lineage, the Lepus spp. sL and S. floridanus sS. Both the European rabbit and the Lepus europaeus use a third lineage, VH n, in a low proportion of their VDJ rearrangements. The VH n genes are a conserved ancestral polymorphism that is being maintained in the leporid genome.Their usage in a low proportion of VDJ rearrangements by both European rabbit and L. europaeus but not S. floridanus has been argued to be a remnant of an ancient European leporid immunologic response to pathogens. To address this hypothesis, in this study we sequenced VDJ rearranged genes for another North American leporid, L. americanus . Our results show that L. americanus expressed these genes less frequently and in a highly modified fashion compared to the European Lepus species. Our results suggest that the American leporid species use a different VH repertoire than the European species which may be related with an immune adaptation to different environmental conditions, such as different pathogenic agents.